Visibilization and Parental Pin. A challenge for educational institutions in Mexico. - Vázquez Parra, José Carlos (2022)
The purpose of this paper is to reflect on the parental pin proposal that limits access to information on sexual and gender diversity for students in their educational institutions. Under the argument that these issues are the responsibility of families, a discourse is constructed that qualifies that these issues generate uncertainty in young people and can confuse them in their development. Therefore, this study with mixed methodology shows the level of awareness of a sample group of young people in middle and higher education about the importance of access to issues related to sexual and gender diversity, within their process of building their identity and personality development. Based on a mixed instrument, it is concluded that access to information is a right and a legitimate demand of young people, questioning the validity and justification of the parental pin.